Development of Learning Media Pocket Book Digital SKI Material Islamic Civilization Umayyad State in Damascus Class X Madrasah Aliyah - Nila Abidatum Munafiatin; Alaika Abdi Muhammad; Ahmad Mustofa Lutfi (Kasyafa: Jurnal Pendidikan Agama Islam, 2025)
The rapid development of technology requires teachers to innovate and utilize technology to support the learning process, one of which is by utilizing digital pocket books as a learning medium, so that the learning process becomes varied and not boring. In SKI learning, teachers often use the lecture method with learning media in the form of printed books/LKS without other media, which makes students feel bored because of the monotonous learning atmosphere and the lack of innovation in the learning media used. This study aims to determine the development process and feasibility of the SKI digital pocket book learning media. This type of research is Research and Development (R&D) with the ADDIE model, including analysis, design, development, implementation and evaluation. Data collection was carried out using observation, interview, questionnaire and documentation techniques. The data analysis technique in this study is a descriptive statistical data analysis technique using a Likert scale. The results of the study showed that the SKI digital pocket book had very feasible criteria, the design aspect obtained a value of 94.9%, the readability aspect obtained a value of 94.4%, the material aspect obtained a value of 98.8% and the practicality aspect obtained a value of 95.2%. Thus, the SKI digital pocket book learning media for the material of Islamic civilization of the Umayyad Daulah in Damascus for class X MA Al Arqom Sarirejo Bojonegoro has been tested for its validity and practicality and is feasible to be used when learning.